Estudio de factibilidad para la creación de una guardería para servicios de mascotas, Ibarra, Imbabura - Landazuri Peñaherrera, Evelyn Daniela (2023)
The present research work is based on a feasibility study for the creation of a nursery for pet services, in the city of Ibarra for which it has been analyzed that it is an indispensable project for society in the long term, since they are currently being created in different parts of the city. Today Ibarra families have a pet in their home, they usually have a pet at home. However, many of these families when they have to travel, take their pet with them or entrust it to a family member with the well-known problems that may arise. The feasibility study is responsible for determining and studying the different factors of competition, and verifying whether the research plan is feasible or not. The objective of the elaboration of this project is to demonstrate the feasibility of its creation, taking into account the elements of market study, technical study, legal study and financial study. Guaranteeing success in the planning of this company: in addition to offering the client these services for consented pets with innovative services and at an affordable price to meet the needs of the client. We will analyze the results and feasibility of the project to begin with the execution of the same offering a service of excellent quality and at a profitable and competitive price.